INTERCULTURAL COMMUNICATION IN THE TRILOGY OF RUSH HOUR - I Gede Agus Sastrawan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Intercultural communication (ICC) is a dynamic communicative phenomenon due to the cultural value presented in the multicultural communication exchange. The present study aims to explore the intercultural communication between Black and Chinese speakers in the trilogy of Rush Hour. Specifically, this study aims to see the characteristics of Black English and the communicative effects of conversation among speakers of different cultural backgrounds. Through the methods of qualitative descriptive, linguistic behavior is justified to show whether the conventions are acceptable to each community group. The results show that as an American English-speaking, Carter, a Black American is more expressive in using English because he is a native speaker, while Lee, as an L2 English from China, faces more communicative barriers. The cultural value of non-standard forms also adorns such conversation, e.g., phonological and sentence structures stigmatization. Not to mention, Chinese surnames produce homonyms with English pronouns.